The Influence of Spin-Labeled Fluorene Compounds on the Assembly and Toxicity of the Aβ Peptide - Petrlova, Jitka; Kálai, Tamás; Maezawa, Izumi; Altman, Robin; Harishchandra, Ghimire; Hong, Hyun-Seok; Bricarello, Daniel A.; Parikh, Atul N.; Lorigan, Gary A.; Jin, Lee-Way; Hideg, Kálmán; Voss, John C. (PLOS ONE, 2012)
Background The deposition and oligomerization of amyloid β (Aβ) peptide plays a key role in the pathogenesis of Alzheimer's disease (AD). Aβ peptide arises from cleavage of the membrane-associated domain of the amyloid precursor protein (APP) by β and γ secretases. Several lines of evidence point to the soluble Aβ oligomer (AβO) as the primary neurotoxic species in the etiology of AD. Recently, we have demonstrated that a class of fluorene molecules specifically disrupts the AβO species. Methodology/Principal Findings To achieve a better understanding of the mechanism of action of this disruptive ability, we extend the application of electron paramagnetic resonance (EPR) spectroscopy of site-directed spin labels in the Aβ peptide to investigate the binding and influence of fluorene compounds on AβO structure and dynamics. In addition, we have synthesized a spin-labeled fluorene (SLF) containing a pyrroline nitroxide group that provides both increased cell protection against AβO toxicity and a route to directly observe the binding of the fluorene to the AβO assembly. We also evaluate the ability of fluorenes to target multiple pathological processes involved in the neurodegenerative cascade, such as their ability to block AβO toxicity, scavenge free radicals and diminish the formation of intracellular AβO species. Conclusions Fluorene modified with pyrroline nitroxide may be especially useful in counteracting Aβ peptide toxicity, because they posses both antioxidant properties and the ability to disrupt AβO species.